Primavera silenciosa, de Rachel Carson: más de medio siglo después - Falla, Gabriel; Esquivel, Juan Pablo; Aldana, Laura; Coronel, Geraldine; Velasco, María Alejandra; Franco, Ricardo; Pérez, Royman (Boletín P.P.D.Q., 2021)
Primavera silenciosa, de Rachel Carson: más de medio siglo después